2008
DOI: 10.3748/wjg.14.4370
|View full text |Cite
|
Sign up to set email alerts
|

Orthotopic liver transplantation as a rescue operation for recurrent hepatocellular carcinoma after partial hepatectomy

Abstract: There are no significant differences in survival/mortality rates between OLT as de novo therapy and OLT as a rescue therapy for patients with hcc. Pre-OLT hyperbilirubinemia, post-OLT requirement of transfusion, large tumor size and family history of HCC are associated with a poor survival outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…The remaining 16 articles were included for this review, as outlined in the PRISMA flow diagram (Fig. ) . None of the studies reviewed were randomized trials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 16 articles were included for this review, as outlined in the PRISMA flow diagram (Fig. ) . None of the studies reviewed were randomized trials.…”
Section: Resultsmentioning
confidence: 99%
“…1). [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] None of the studies reviewed were randomized trials. There was a combination of class II (nonrandomized comparative or well-designed cohort studies) and class III (observational studies) evidence in the available literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Barcelona Clinic Liver Cancer (BCLC) approach, resection is the treatment of choice in patients with limited tumor size and normal bilirubin levels as well as absence of portal hypertension [22]. In these patients, rescue OLT is feasible in case of recurrent or de novo liver cancer fulfilling the Milan criteria [23]. In contrast, in patients with (very) early stage HCC, but impaired liver function, OLT is recommended as primary treatment approach [24].…”
Section: Risk Factors For Recurrencementioning
confidence: 99%
“…In an attempt to promote LR as the first‐line treatment with curative intention, salvage transplantation following LR in cases of disease recurrence has been widely adopted . The initial reports by Majno et al and Poon et al were followed by several contributions . Initial concerns regarding the technical difficulties of LT after LR were discarded, and a recent meta‐analysis evaluating the outcomes of this strategy confirmed that salvage LT following primary LR is a highly applicable strategy with long‐term survival outcomes that are comparable to upfront LT …”
mentioning
confidence: 99%